Implementasi Good Corporate Governance sebagai Instrumen Pencegahan Korupsi dalam Dunia Usaha - Via Nurita Dolok Saribu; Marwan Parulian Simanjuntak; Yohanes Andis Arya Panca Putra (LPPM Universitas Widya Dharma Pontianak, 2026)
Corruption remains one of the major challenges in creating a healthy, transparent, and sustainable business environment in Indonesia. Corrupt practices in the business sector not only cause economic losses but also reduce the confidence of investors, society, and stakeholders in corporate integrity. One of the strategic approaches to preventing corruption is the implementation of Good Corporate Governance (GCG). This study aims to analyze the implementation of Good Corporate Governance as an instrument for corruption prevention in the business sector and to examine the role of corporate compliance culture in strengthening the effectiveness of GCG implementation. This research employs a normative legal research method using statutory and conceptual approaches. The legal materials consist of primary, secondary, and tertiary legal sources, which are analyzed qualitatively. The findings indicate that the implementation of the principles of transparency, accountability, responsibility, independence, and fairness can strengthen corporate internal control systems and reduce opportunities for corruption. Furthermore, corporate compliance culture, whistleblowing systems, and the implementation of ISO 37001 Anti-Bribery Management Systems play significant roles in enhancing corruption prevention efforts. Therefore, strengthening corporate governance and compliance culture is essential to creating an ethical, accountable, and corruption-free business environment. Keywords: Good Corporate Governance, Corruption, Corporate Compliance Culture, Corporate Governance, Business Law.